Syntactic Templates of the Clause in Central Kurdish According to Role and Reference Grammar (Raparin Journal of Humanities (RJH), 2020)
Clause in Role and Reference Grammar has a layered structure (LS) which is based on two fundamental distinctions: the distinction between the argument and the predicate on the one hand, and the distinction between the argument and the non-argument constituents of the clause on the other hand. The aim of this research is to study the syntactic templates of the clause in Central Kurdish simple sentences according to Role and Reference Grammar. Data are analyzed by following Van Valin´s framework and besides them, the researchers' intuition, as the native speakers of the accent plays a decisive role in evaluating the data. The research´s findings include: categorizing the CKD’s predicates into two groups of verbal and non-verbal predicates, dividing the verbal predicates based on the number of their arguments, defining the non-verbal predicates according to the part of speech of their arguments, and finally, introducing the non-universal elements in CKD’s clause structure.